1998
DOI: 10.1016/s0960-9822(07)00488-5
|View full text |Cite
|
Sign up to set email alerts
|

High cancer susceptibility and embryonic lethality associated with mutation of the PTEN tumor suppressor gene in mice

Abstract: The mPTEN gene is fundamental for embryonic development in mice, as mPTEN3-5 mutant embryos died by day 9.5 of gestation, with patterning defects in cephalic and caudal regions and defective placentation. Heterozygous mice developed lymphomas associated with loss of heterozygosity of the wild-type mPTEN allele, and tumor appearance was accelerated by gamma-irradiation. These lymphomas had high levels of activated Akt/PKB, the protein product of a murine proto-oncogene with anti-apoptotic function, associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
580
1
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 749 publications
(608 citation statements)
references
References 39 publications
23
580
1
4
Order By: Relevance
“…Germ-line mutations of PTEN have also been suggested as the underlying genetic lesion in Cowden disease , an inherited autosomal syndrome characterized by increased incidence of breast and thyroid tumors; and in Bannaya-Zonana Syndrome, a disorder characterized by intestinal hamartomas and neurological abnormalities . In vivo studies in mouse models have demonstrated that heterozygous PTEN disruption causes hyperplastic-dysplastic changes in the prostate, skin and colon, similar to those observed in Cowden disease (Di Cristofano et al, 1998;Suzuki et al, 1998), providing additional evidence for the role of PTEN in tumor suppression.…”
Section: Discussionmentioning
confidence: 68%
“…Germ-line mutations of PTEN have also been suggested as the underlying genetic lesion in Cowden disease , an inherited autosomal syndrome characterized by increased incidence of breast and thyroid tumors; and in Bannaya-Zonana Syndrome, a disorder characterized by intestinal hamartomas and neurological abnormalities . In vivo studies in mouse models have demonstrated that heterozygous PTEN disruption causes hyperplastic-dysplastic changes in the prostate, skin and colon, similar to those observed in Cowden disease (Di Cristofano et al, 1998;Suzuki et al, 1998), providing additional evidence for the role of PTEN in tumor suppression.…”
Section: Discussionmentioning
confidence: 68%
“…Inactivation mutation in mice reveal a necessary function for Pten during embryogenesis, but a percentage of heterozygous mice also show colonic carcinomas (Di Cristofano et al, 1998;Suzuki et al, 1998).…”
Section: Mouse Models For Hnpccmentioning
confidence: 99%
“…As an aside, prostatic hyperplasia (but not neoplasia) also has been observed after the targeted inactivation of various tumor suppressor genes including nkx3.1 (Bhatia-Gaur et al, 1999), p27kip1 (Cordon-Cardo et al, 1998), pten (Di Cristofano et al, 1998;Podsypanina et al, 1999;Suzuki et al, 1998), estrogen receptor beta (Krege et al, 1998), and mxi1 (Schreiber-Agus et al, 1998). Finally, since the techniques associated with the MPR model are challenging, this system has been exploited thus far primarily by its originators (Buttyan, 1997;Green et al, 1998).…”
Section: Future Directionsmentioning
confidence: 99%